A rubber composite material for water stop and preparation method thereof
By using natural rubber and polybutadiene rubber in the microwave hot air vulcanization process of rubber water stop, and adding specific fillers and aid crosslinking agent, the size retention and stability of natural rubber during vulcanization is solved, and better shape retention, anti-vulcanization return and elastic sealing effects are achieved.
Patent Information
- Application Number
- CN202211695868.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-28
AI Technical Summary
In the microwave hot air vulcanization process, natural rubber has poor appearance dimensional retention and poor vulcanization stability, resulting in reduced mechanical properties and permanent compression deformation.
Natural rubber and polybutadiene rubber are used as the main components, and carbon black, white carbon black, inorganic cost-reducing fillers, crosslinking agents and other components are added, and crosslinking agents are added during the master refining stage to increase the modulus of the rubber and Mooney's viscosity through slight crosslinking.
The shape retention, dimensional stability and anti-vulcanization return ability of the rubber water stop are significantly improved, and the elasticity and waterproofing effect of the material are improved.
Smart Images

Figure BDA0004023409210000101 
Figure BDA0004023409210000111 
Figure BDA0004023409210000112
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of rubber composite materials, and more specifically, relates to a rubber composite material for a waterstop and a preparation method thereof. Background Art
[0002] Rubber waterstop is an important component of polymer waterproof materials used in engineering. It mainly uses the elastic characteristics of rubber materials to achieve the effect of elastic sealing and waterproofing. It is mainly used in deformation joints and construction joints of engineering projects. Specific application areas include underground facilities, subways, tunnels, culverts, water supply aqueducts, dams and liquid storage structures.
[0003] The vulcanization molding processes of rubber waterstop mainly include compression vulcanization process and microwave hot air vulcanization process. The compression vulcanization process uses pressure to make the rubber material directly contact with the heated mold, and the contact heat transfer makes the rubber reach the required molding vulcanization temperature. The microwave hot air vulcanization process, on the one hand, uses microwave-assisted heating to carry out preliminary vulcanization and appearance dimensional finalization, and on the other hand, mainly relies on hot air heat transfer to make the product reach the required vulcanization temperature. The heat transfer efficiency of hot air is lower than the contact heat transfer efficiency of the compression vulcanization process. In order to improve production efficiency, the temperature of hot air must be higher than the optimal vulcanization temperature of rubber. At the same time, compared with the compression vulcanization process, the extrusion molding plus microwave hot air vulcanization process is widely used by manufacturers due to its high production efficiency.
[0004] The rubber waterstop produced by microwave hot air vulcanization process is traditionally produced with EPDM rubber. EPDM rubber has good high temperature resistance and good anti-vulcanization reversion ability, and can adapt to higher hot air vulcanization temperatures. At the same time, high Mooney, medium and high ethylene content EPDM rubber can be filled with a large amount of reinforcing materials and inorganic cost-reducing fillers, so that it has a higher modulus during the microwave hot air vulcanization scorch period, and the shape and size retention rate is high; the molded vulcanization waterstop has mold shaping during the vulcanization process, and there is no collapse and deformation of the waterstop.
[0005] Natural rubber has excellent mechanical properties and elasticity, and is widely used in rubber waterstops produced by microwave hot air vulcanization. However, compared with EPDM extruded waterstops, natural rubber has the disadvantages of poor appearance dimensional retention and poor vulcanization stability during the production process of extruded microwave hot air vulcanization. This is because the natural rubber molecular chain contains a large number of double bonds with low bond energy and high unsaturation, which causes the thermal stability of natural rubber to be poor. Under high production rates, in order to ensure sufficient vulcanization, the vulcanization temperature needs to be increased, which will lead to obvious vulcanization reversion, and then lead to a decrease in the mechanical properties and compression permanent deformation properties of natural rubber; at the same time, the formula with natural rubber as the main raw rubber component, in the early stage of microwave hot air vulcanization production, the modulus of the rubber material is sharply reduced under high temperature environment, and at this time, the rubber material has not undergone sufficient cross-linking to shape the product, and the waterstop is prone to collapse or distortion, affecting the appearance quality of the product. Summary of the invention
[0006] The purpose of the present invention is to provide a rubber composite material for a waterstop and a preparation method thereof. The rubber composite material for a waterstop of the present invention uses natural rubber as the main raw rubber. The rubber composite material for a waterstop has good appearance shape retention during the microwave hot air vulcanization process for preparing the rubber waterstop, and has good anti-vulcanization reversion ability during the high-temperature vulcanization process.
[0007] In order to achieve the above-mentioned object, the present invention provides a rubber composite material for a waterstop strip, and the raw materials for preparing the rubber composite material for a waterstop strip include: rubber, carbon black, white carbon black, inorganic cost-reducing filler, co-crosslinking agent, activator, antioxidant, plasticizer, vulcanizer and accelerator;
[0008] The rubber is natural rubber and polybutadiene rubber.
[0009] According to the present invention, preferably, in parts by weight, the amount of the natural rubber is 70-90 parts, the amount of the polybutadiene rubber is 10-30 parts, the amount of the carbon black is 20-75 parts, the amount of the white carbon black is 5-25 parts, the amount of the inorganic cost-reducing filler is 20-130 parts, the amount of the co-crosslinking agent is 0.5-3.0 parts, the amount of the activator is 3.5-9 parts, the amount of the antioxidant is 2-7 parts, the amount of the plasticizer is 1.5-15.0 parts, the amount of the vulcanizer is 0.4-1.6 parts, and the amount of the accelerator is 0.6-2.5 parts.
[0010] In the present invention, the amount of the polybutadiene rubber is preferably 15-25 parts.
[0011] According to the present invention, preferably, the polybutadiene rubber is polybutadiene rubber and / or polybutadiene rubber whose terminal is modified by imide ions.
[0012] In the present invention, polybutadiene rubber with imide ion modified molecular chain ends is preferably used, which can improve the dispersibility of carbon black and white carbon black as island phase seeds, and significantly improve the elasticity of the material. The principle is: the terminal imide ion of the modified polybutadiene rubber can improve the affinity with carbon black, thereby improving the dispersibility of the filler as an island phase seed. After the affinity of the molecular chain end with carbon black is enhanced, the slip creep of the rubber molecular chain can be effectively limited during the rubber compression process, thereby significantly improving the elasticity of the material, that is, improving the compression permanent deformation index. At the same time, during the rubber mixing process, the molecular chain end has a strong interaction with the filler, which will increase the Mooney viscosity and modulus of the rubber to a certain extent, thereby improving the shape retention rate and dimensional stability of the rubber.
[0013] According to the present invention, preferably, the carbon black is carbon black N550 and optionally other carbon blacks;
[0014] The other carbon black comprises at least one of carbon black N330, carbon black N774 and carbon black N660;
[0015] In parts by weight, the amount of the carbon black N550 is 20-50 parts, and the amount of the other carbon black is 0-25 parts.
[0016] According to the present invention, preferably, the white carbon black is precipitated white carbon black, and the BET specific surface area of the white carbon black is 160-180m 2 / g.
[0017] In the present invention, white carbon black is polar and natural rubber is non-polar. Generally, when white carbon black is used in natural rubber, in order to improve the dispersibility and reinforcing effect of polar white carbon black in non-polar natural rubber, the white carbon black is surface-modified. If the white carbon black is not surface-modified, the white carbon black will re-aggregate during the storage or vulcanization of the rubber compound to produce a flocculation effect, which is manifested as an increase in the modulus and Mooney viscosity of the rubber compound. The increase in modulus and Mooney viscosity will improve the stiffness and anti-collapse ability of natural rubber in the microwave hot air vulcanization process, thereby enabling the product to obtain good shape retention and dimensional stability.
[0018] In the present invention, the amount of white carbon black used is preferably controlled within 25 parts. Although unmodified white carbon black will have a certain impact on the performance of the formula, within the amount range of white carbon black used in the present invention, the overall performance of the formula still far exceeds the requirements of the national standard and railway industry standard waterstop.
[0019] According to the present invention, preferably, the inorganic cost-reducing filler is at least one of calcium carbonate, kaolin and silica powder.
[0020] In the present invention, the inorganic cost-reducing fillers calcium carbonate, kaolin and silica powder also have a certain flocculation effect, but the degree of their flocculation effect is significantly lower than that of white carbon black. Therefore, the addition of inorganic cost-reducing fillers is also beneficial to a certain extent for the product to obtain good shape retention and dimensional stability.
[0021] According to the present invention, preferably, the auxiliary cross-linking agent is N,N′-m-phenylene bismaleimide.
[0022] According to the present invention, preferably, the activator is composed of zinc oxide and stearic acid; in parts by weight, the amount of zinc oxide is 2.5-6 parts, and the amount of stearic acid is 1-3 parts;
[0023] The antioxidant is composed of a chemical antioxidant and a physical antioxidant; the chemical antioxidant is at least one of a quinoline antioxidant, a p-phenylenediamine antioxidant and a thiourea antioxidant; the physical antioxidant is microcrystalline wax and / or paraffin; in parts by weight, the amount of the chemical antioxidant is 1.5-4 parts, and the amount of the physical antioxidant is 0.5-3 parts;
[0024] The quinoline antioxidant is preferably at least one of antioxidant RD, antioxidant BLE and antioxidant AW; the p-phenylenediamine antioxidant is preferably at least one of antioxidant 4010, antioxidant 4010NA, antioxidant 4020, antioxidant DNP and antioxidant 4030; the thiourea antioxidant is preferably antioxidant CTU;
[0025] The plasticizer is naphthenic oil and / or paraffin oil, and the Cleveland flash point of the plasticizer is 190-280°C;
[0026] The vulcanizing agent is sulfur;
[0027] The accelerator is a sulfenamide accelerator and optionally other accelerators;
[0028] The xanthocyanamide accelerator is at least one of accelerator CBS, accelerator NS, accelerator DZ and accelerator AZ;
[0029] The other accelerator is a thiazole accelerator and / or a thiuram accelerator; the thiazole accelerator is preferably an accelerator DM; the thiuram accelerator is preferably at least one of accelerator TMTD, accelerator TRA, accelerator TBzTD and accelerator TETD;
[0030] In parts by weight, the amount of the sulfonamide accelerator is 0.6-1.5 parts, and the amount of the other accelerator is 0-1 parts.
[0031] Another aspect of the present invention provides a method for preparing the rubber composite material for the waterstop strip, the preparation method comprising:
[0032] (1) plasticating the rubber in an internal mixer;
[0033] (2) then adding the carbon black, the white carbon black, the inorganic cost-reducing filler and the auxiliary cross-linking agent and mixing;
[0034] (3) adding the activator, the antioxidant and the plasticizer again, mixing and removing the rubber, and obtaining a masterbatch;
[0035] (4) The masterbatch, the vulcanizing agent and the accelerator are mixed and discharged in an internal mixer to obtain a final rubber mix.
[0036] The cross-linking aid of the rubber for waterstop is generally added in the final rubber mixing process, which can improve the heat resistance, anti-vulcanization reversion ability and mechanical properties of the product; however, the present invention changes the feeding order of the cross-linking aid in the process, and adds it in the masterbatch mixing stage, utilizing its cross-linking property to improve the shape retention and dimensional stability of the rubber during microwave hot air vulcanization.
[0037] For example, taking the auxiliary cross-linking agent N,N′-m-phenylene bismaleimide (PDM or HVA-2 for short) as an example, its principle is further explained as follows: when N,N′-m-phenylene bismaleimide is added to the final rubber, due to the low processing temperature, no cross-linking reaction will occur; however, when it is added to the masterbatch mixing process, due to the high temperature of the masterbatch process, the cross-linking reaction of the auxiliary agent will be initiated in advance. The auxiliary cross-linking agent can be slightly cross-linked in the masterbatch mixing process. The slight cross-linking can increase the modulus and Mooney viscosity of the rubber without affecting the processing fluidity of the rubber, thereby improving the stiffness and anti-collapse ability of natural rubber in the microwave hot air vulcanization process; through the above method, not only the heat resistance, anti-vulcanization reversion ability and mechanical properties of the formula are improved, but also the shape retention rate and dimensional stability of the rubber are improved.
[0038] According to the present invention, preferably, in step (1), the plasticating is performed at a rotation speed of 30-45 rpm for 30-40 seconds;
[0039] In step (2), mixing to 105-110° C. at a rotation speed of 30-45 rpm;
[0040] In step (3), mixing at a rotation speed of 30-45 rpm to a temperature of 125-140° C., and removing the rubber to obtain a masterbatch;
[0041] In step (4), the mixture is mixed at a rotation speed of 20-30 rpm to a temperature of 90-100° C., and the rubber is discharged to obtain a final rubber mixture.
[0042] In the present invention, the mixing temperature of the masterbatch is preferably less than 140° C. to prevent excessive crosslinking from causing a sharp increase in the Mooney viscosity and modulus of the rubber compound, resulting in a loss of the rubber compound's suitable processing fluidity.
[0043] The technical solution of the present invention has the following beneficial effects:
[0044] (1) Conventional silica is subjected to surface modification during use to improve the dispersibility of silica in rubber. However, the present invention does not modify silica. Instead, when a small amount of silica is used, the modulus of the rubber during the vulcanization heating process is appropriately increased through the flocculation effect of silica and inorganic cost-reducing fillers; thereby improving the stiffness and shape retention of the formula with natural rubber as the main raw rubber component during microwave hot air vulcanization.
[0045] (2) In the present invention, the cross-linking aid is added during the mixing stage of the masterbatch. Preferably, the temperature of the mixing stage is controlled so that the masterbatch is slightly cross-linked during the mixing stage. The modulus and Mooney viscosity of the rubber are increased without affecting the processing fluidity of the rubber. The stiffness and shape retention of the formula with natural rubber as the main raw rubber component during the microwave hot air vulcanization process are further improved.
[0046] (3) Significantly improve the elasticity of the material (improve the compression permanent deformation index) and improve the elastic sealing effect of the rubber waterstop. Rubber is one of the main drainage materials, and its elastic sealing effect is mainly used to achieve it. Therefore, the elasticity of the rubber material is crucial to the waterproof effect. The present invention preferably introduces polybutadiene rubber with imide ion modified at the end of the molecular chain while using a co-crosslinking agent to improve the elasticity of the material. By improving the interaction between the end of the molecular chain and the filler, the molecular chain slip creep of the rubber molecular chain during the compression process is further limited, the compression permanent deformation index deterioration (elasticity deterioration) caused by the molecular chain slip creep is reduced, and the waterproof effect of the rubber material in elastic sealing is improved.
[0047] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0048] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0049] The present invention is further described below by examples:
[0050] The white carbon black used in the following examples and comparative examples is precipitated white carbon black, and the BET specific surface area of white carbon black is 170 m 2 / g; the auxiliary crosslinking agent used is N,N′-m-phenylene bismaleimide; the vulcanizing agent used is sulfur; the inorganic cost-reducing filler used is calcium carbonate; the plasticizer used is cyclohexane oil, and the Cleveland flash point of the plasticizer is 230°C;
[0051] The polybutadiene rubber used was purchased from Daqing Petrochemical Company of China National Petroleum Corporation, with the brand name BR9000; the polybutadiene rubber with terminal imide ion modification used was BR1250H from Japan Zeon;
[0052] The activator used is composed of zinc oxide and stearic acid, in which the amount of zinc oxide is 4 parts and the amount of stearic acid is 2 parts by weight; wherein the stearic acid is purchased from Nantong Kangqiao Oil Co., Ltd., with a brand number of 1840;
[0053] In terms of weight, the antioxidant used is composed of 1 part of antioxidant RD, 1 part of antioxidant 4010NA, 1 part of antioxidant CTU and 1 part of microcrystalline wax;
[0054] In terms of weight, the accelerator used consists of 1 part of accelerator CBS, 0.5 part of accelerator DM and 0.2 part of accelerator TBzTD.
[0055] Example 1
[0056] The formula of this embodiment is shown in Table 1;
[0057] The specific preparation method is as follows:
[0058] 1) natural rubber and polybutadiene rubber BR9000 were put into an internal mixer and plasticized for 35 seconds at a rotation speed of 40 rpm;
[0059] 2) Add carbon black N550, white carbon black, inorganic cost-reducing filler and co-crosslinking agent, and mix at a speed of 40 rpm to 100° C.;
[0060] 3) Add activator, antioxidant and plasticizer, mix at a rotation speed of 40 rpm to 135° C., discharge the rubber, and obtain a masterbatch after cooling.
[0061] 4) The masterbatch, vulcanizing agent and accelerator are put into an internal mixer, mixed to 95° C. at a rotation speed of 25 rpm, discharged, and the final rubber mixture is obtained after cooling.
[0062] Example 2
[0063] The formula of this embodiment is shown in Table 1;
[0064] The specific preparation method is as follows:
[0065] 1) natural rubber and polybutadiene rubber BR9000 were put into an internal mixer and plasticized for 35 seconds at a rotation speed of 40 rpm;
[0066] 2) Add carbon black N550, white carbon black, inorganic cost-reducing filler and co-crosslinking agent, and mix at a speed of 40 rpm to 100° C.;
[0067] 3) Add activator, antioxidant and plasticizer, mix at a rotation speed of 40 rpm to 135° C., discharge the rubber, and obtain a masterbatch after cooling.
[0068] 4) The masterbatch, vulcanizing agent and accelerator are put into an internal mixer, mixed to 95° C. at a rotation speed of 25 rpm, discharged, and the final rubber mixture is obtained after cooling.
[0069] Example 3
[0070] The formula of this embodiment is shown in Table 1;
[0071] The specific preparation method is as follows:
[0072] 1) natural rubber and polybutadiene rubber BR9000 were put into an internal mixer and plasticized for 35 seconds at a rotation speed of 40 rpm;
[0073] 2) Add carbon black N550, white carbon black, inorganic cost-reducing filler and co-crosslinking agent, and mix at a speed of 40 rpm to 100° C.;
[0074] 3) Add activator, antioxidant and plasticizer, mix at a rotation speed of 40 rpm to 135° C., discharge the rubber, and obtain a masterbatch after cooling.
[0075] 4) The masterbatch, vulcanizing agent and accelerator are put into an internal mixer, mixed to 95° C. at a rotation speed of 25 rpm, discharged, and the final rubber mixture is obtained after cooling.
[0076] Example 4
[0077] The formula of this embodiment is shown in Table 1;
[0078] The specific preparation method is as follows:
[0079] 1) natural rubber and polybutadiene rubber BR1250H with imide ion modified at the end were put into an internal mixer and plasticized for 35 seconds at a rotation speed of 40 rpm;
[0080] 2) Add carbon black, white carbon black, inorganic cost-reducing filler and co-crosslinking agent, and mix at a speed of 40 rpm to 100° C.;
[0081] 3) Add activator, antioxidant and plasticizer, mix at a rotation speed of 40 rpm to 135° C., discharge the rubber, and obtain a masterbatch after cooling.
[0082] 4) The masterbatch, vulcanizing agent and accelerator are put into an internal mixer, mixed to 95° C. at a rotation speed of 25 rpm, discharged, and the final rubber mixture is obtained after cooling.
[0083] Example 5
[0084] The formula of this embodiment is shown in Table 1;
[0085] The specific preparation method is as follows:
[0086] 1) natural rubber and polybutadiene rubber BR9000 are put into an internal mixer and plasticized for 30-40 seconds at a speed of 30-45 rpm;
[0087] 2) Add carbon black, white carbon black and inorganic cost-reducing filler, and mix at a speed of 40 rpm to 100° C.;
[0088] 3) Add activator, antioxidant and plasticizer, mix at a rotation speed of 40 rpm to 135° C., discharge the rubber, and obtain a masterbatch after cooling.
[0089] 4) The masterbatch, co-crosslinking agent, vulcanizing agent and accelerator are put into an internal mixer, mixed to 95° C. at a rotation speed of 25 rpm, discharged, and cooled to obtain the final rubber mix.
[0090] Comparative Example 1
[0091] The formula of this comparative example is shown in Table 1;
[0092] The specific preparation method is as follows:
[0093] 1) natural rubber and polybutadiene rubber BR9000 were put into an internal mixer and plasticized for 35 seconds at a rotation speed of 40 rpm;
[0094] 2) Add carbon black N550 and inorganic cost-reducing filler, and mix at a speed of 40 rpm to 100° C.;
[0095] 3) Add activator, antioxidant and plasticizer, mix at a rotation speed of 40 rpm to 135° C., discharge the rubber, and obtain a masterbatch after cooling.
[0096] 4) The masterbatch, co-crosslinking agent, vulcanizing agent and accelerator are put into an internal mixer, mixed to 95° C. at a rotation speed of 25 rpm, discharged, and cooled to obtain the final rubber mix.
[0097] Table 1 Comparative Examples and Example Formulas (Amounts in the table are all parts by weight)
[0098]
[0099]
[0100] Test Example 1
[0101] The above embodiments and comparative examples were tested, and the specific test results are shown in the following table. Among them, MH and ML were tested according to GB / T9869-2014, the test temperature was 165°C, and the test time was 15 minutes; Mooney viscosity was tested according to GB / T 1232.1-2016, and the test condition was ML (1+4) 100°C; vulcanization reversion rate = (MH-Mt) / (MH-ML)×100%.
[0102] Table 2 Comparative Examples and Examples Rheometer and Mooney Viscometer Test Data (165°C*15min)
[0103]
[0104]
[0105] It can be seen from the above table that: compared with Example 1 and Example 5, the addition of the co-crosslinking agent in the final rubber mix can significantly improve the MH, ML and Mooney viscosities compared to the addition in the masterbatch.
[0106] Compared with Comparative Example 1, Example 5 shows that white carbon black increases MH, ML and Mooney viscosity.
[0107] Analysis of the data in Table 2 shows that the addition of white carbon black and the addition of a vulcanizing agent in the masterbatch stage will significantly increase the modulus and Mooney viscosity of the rubber compound. This is because white carbon black and other inorganic cost-reducing fillers will re-aggregate and produce a flocculation effect during the storage of the final rubber mix. At the same time, a flocculation effect will also occur during the vulcanization heating, resulting in an increase in the modulus and Mooney viscosity of the final rubber mix; the addition of a cross-linking agent in the first stage not only increases the modulus of the rubber compound, but also improves the anti-vulcanization reversion ability of the final rubber mix.
[0108] Test Example 2
[0109] The above embodiments and comparative examples were tested, and specific test results are shown in the table below; wherein, the Shore A hardness was tested according to GB / T531.1-2008; the tensile strength and elongation at break were tested according to GB / T 528-2009, using a type II specimen, a tensile rate of (500±50) mm / min, and an initial gauge length of 20 mm; the compression set was tested according to GB / T 7759.1-2015, using a type B specimen, and a compression rate of 25%.
[0110] Table 3 Mechanical properties and compression set index
[0111]
[0112]
[0113] It can be seen from the above table that: there is no significant change in the mechanical properties, but the compression set is significantly improved.
[0114] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A rubber composite material for a waterstop, characterized in that: The raw materials for preparing the rubber composite material for the water stop belt include: rubber, carbon black, white carbon black, inorganic cost-reducing filler, co-crosslinking agent, activator, antioxidant, plasticizer, vulcanizer and accelerator; The rubber is natural rubber and polybutadiene rubber; The preparation method of the rubber composite material for the waterstop comprises: (1) plasticating the rubber in an internal mixer; (2) then adding the carbon black, the white carbon black, the inorganic cost-reducing filler and the auxiliary cross-linking agent and mixing; (3) adding the activator, the antioxidant and the plasticizer again, mixing and removing the rubber, and obtaining a masterbatch; (4) The masterbatch, the vulcanizing agent and the accelerator are mixed and discharged in an internal mixer to obtain a final rubber mix.
2. The rubber composite material for waterstop according to claim 1, wherein: In parts by weight, the amount of the natural rubber is 70-90 parts, the amount of the polybutadiene rubber is 10-30 parts, the amount of the carbon black is 20-75 parts, the amount of the white carbon black is 5-25 parts, the amount of the inorganic cost-reducing filler is 20-130 parts, the amount of the co-crosslinking agent is 0.5-3.0 parts, the amount of the activator is 3.5-9 parts, the amount of the antioxidant is 2-7 parts, the amount of the plasticizer is 1.5-15.0 parts, the amount of the vulcanizer is 0.4-1.6 parts, and the amount of the accelerator is 0.6-2.5 parts.
3. The rubber composite material for waterstop according to claim 1 or 2, wherein: The polybutadiene rubber is polybutadiene rubber and / or polybutadiene rubber whose terminal is modified by imide ions.
4. The rubber composite material for waterstop according to claim 1 or 2, wherein: The carbon black is carbon black N550 and other optional carbon blacks; The other carbon black comprises at least one of carbon black N330, carbon black N774 and carbon black N660; In parts by weight, the amount of the carbon black N550 is 20-50 parts, and the amount of the other carbon black is 0-25 parts.
5. The rubber composite material for waterstop according to claim 1 or 2, wherein: The white carbon black is precipitated white carbon black, and the BET specific surface area of the white carbon black is 160-180m 2 / g.
6. The rubber composite material for waterstop according to claim 1 or 2, wherein: The inorganic cost-reducing filler is at least one of calcium carbonate, kaolin and silicon powder.
7. The rubber composite material for waterstop according to claim 1 or 2, wherein: The auxiliary cross-linking agent is N,N′-m-phenylene bismaleimide.
8. The rubber composite material for waterstop according to claim 1 or 2, wherein: The activator is composed of zinc oxide and stearic acid; in parts by weight, the amount of zinc oxide is 2.5-6 parts, and the amount of stearic acid is 1-3 parts; The antioxidant is composed of a chemical antioxidant and a physical antioxidant; the chemical antioxidant is at least one of a quinoline antioxidant, a p-phenylenediamine antioxidant and a thiourea antioxidant; the physical antioxidant is microcrystalline wax and / or paraffin; in parts by weight, the amount of the chemical antioxidant is 1.5-4 parts, and the amount of the physical antioxidant is 0.5-3 parts; The plasticizer is naphthenic oil and / or paraffin oil, and the Cleveland flash point of the plasticizer is 190-280°C; The vulcanizing agent is sulfur; The accelerator is a sulfenamide accelerator and optionally other accelerators; The xanthocyanamide accelerator is at least one of accelerator CBS, accelerator NS, accelerator DZ and accelerator AZ; The other accelerators are thiazole accelerators and / or thiuram accelerators; In parts by weight, the amount of the sulfonamide accelerator is 0.6-1.5 parts, and the amount of the other accelerator is 0-1 parts.
9. The rubber composite material for waterstop according to claim 8, wherein: The quinoline antioxidant is at least one of antioxidant RD, antioxidant BLE and antioxidant AW; The p-phenylenediamine antioxidant is at least one of antioxidant 4010, antioxidant 4010NA, antioxidant 4020, antioxidant DNP and antioxidant 4030; The thiourea antioxidant is antioxidant CTU.
10. The rubber composite material for waterstop according to claim 8, wherein: The thiazole accelerator is accelerator DM; The thiuram accelerator is at least one of accelerator TMTD, accelerator TRA, accelerator TBzTD and accelerator TETD.
11. The method for preparing the rubber composite material for waterstop according to any one of claims 1 to 10, characterized in that: The preparation method comprises: (1) plasticating the rubber in an internal mixer; (2) then adding the carbon black, the white carbon black, the inorganic cost-reducing filler and the auxiliary cross-linking agent and mixing; (3) adding the activator, the antioxidant and the plasticizer again, mixing and removing the rubber, and obtaining a masterbatch; (4) The masterbatch, the vulcanizing agent and the accelerator are mixed and discharged in an internal mixer to obtain a final rubber mix.
12. The preparation method according to claim 11, wherein In step (1), the mixture is plasticized at a rotation speed of 30-45 rpm for 30-40 seconds; In step (2), mixing to 105-110° C. at a rotation speed of 30-45 rpm; In step (3), mixing at a rotation speed of 30-45 rpm to a temperature of 125-140° C., and removing the rubber to obtain a masterbatch; In step (4), the mixture is mixed at a rotation speed of 20-30 rpm to a temperature of 90-100° C., and the rubber is discharged to obtain a final rubber mixture.
Citation Information
Patent Citations
Continuous extrusion type rubber waterstop for tunnel and preparation method
CN111471223A